Implementasi Pembelajaran Sains Berbasis Inkuiri dalam Meningkatkan Keterampilan Berpikir Kritis Mahasiswa - Agnes Renostini Harefa (Medan Resource Center, 2026)
The development of critical thinking skills has become a central objective in higher education, particularly in science education, where students are expected to analyze information, evaluate evidence, and make reasoned judgments. However, many university students continue to demonstrate limited critical thinking abilities during the learning process. This study aimed to examine the effectiveness of inquiry-based science learning in enhancing students’ critical thinking skills in the Scientific Learning course. The study involved 20 sixth-semester students enrolled in the Biology Education Study Program at Universitas Nias and employed a one-group pretest–posttest design. Critical thinking skills were measured using a test instrument developed based on Facione’s (1990) critical thinking indicators. The findings revealed a substantial increase in students’ average scores, rising from 54.8 in the pretest to 81.4 in the posttest. The paired-sample t-test produced a significance value of p = 0.000 (p < 0.05), indicating a statistically significant difference between pretest and posttest scores. The overall N-gain score of 0.59 was categorized as moderate, with improvements observed across all critical thinking indicators, although self-regulation showed the lowest gain. These findings demonstrate that inquiry-based science learning effectively enhances university students’ critical thinking skills while highlighting the need for further attention to self-regulation development.